2018
DOI: 10.1136/jech-2017-209701
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence against young women: prevalence and associated factors in Europe

Abstract: Findings show that the fight against violence in young women should consider individual characteristics, childhood experiences of abuse and also structural interventions including reduction of alcohol consumption and improvement in the education-related indicators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
57
6
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 34 publications
(18 reference statements)
9
57
6
2
Order By: Relevance
“…This research was carried out with the participation of 73 women who said they had experienced sexual violence and 37 who said they had not. The sociodemographic data obtained is consistent with the results of other studies also involving women using public support services (Sanabria & Murray, 2018;Sanz-Barbero et al 2018;Yera Alós & Medrano Allieri, 2018), who have insecure employment and social status, are caring for children, and have a low level of education. This may increase the perception of financial and emotional dependence, encourage the victim's family and social isolation and increase the severity of violent physical and sexual behaviour by the aggressor (Martínez-Sanz et al 2016;Rubio-Garay et al 2017;Year,Alós & Medrano Allieri, 2018).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This research was carried out with the participation of 73 women who said they had experienced sexual violence and 37 who said they had not. The sociodemographic data obtained is consistent with the results of other studies also involving women using public support services (Sanabria & Murray, 2018;Sanz-Barbero et al 2018;Yera Alós & Medrano Allieri, 2018), who have insecure employment and social status, are caring for children, and have a low level of education. This may increase the perception of financial and emotional dependence, encourage the victim's family and social isolation and increase the severity of violent physical and sexual behaviour by the aggressor (Martínez-Sanz et al 2016;Rubio-Garay et al 2017;Year,Alós & Medrano Allieri, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…Labrador et al (2010) reported sexual prevalence varying between 20% and 54%. Basile & Hall (2011) and Sanz-Barbero et al (2018) found the prevalence of sexual violence to be 8.8% and noted that it was associated with the financial, social and personal vulnerability of women with children in their care.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the epidemiological studies that analyze the causes and consequences of IPV have been carried out among the general population, [6,7] however, there is increasing scientific evidence that shows an increase in IPV among the young population. [8] A recently published multi-country study (carried out with a representative sample of 28 countries in the European Union) shows a current prevalence of physical and/or sexual IPV in women ages 18–29 of 6.1% (4% among the general population) and a lifetime prevalence of psychological IPV of up to 47.9% (32% among the general population). [5] Also, being in elder ages has been identified as a barrier to leaving a violent relationship.…”
Section: Introductionmentioning
confidence: 99%
“…We foresee several challenges during the implementation and evaluation of this protocol. The first challenge emerges from the fact that we are going to implement and evaluate the same interventions with teachers and students in six European cities which differ in many aspects, including their prevalence rates of dating violence [52]. Although English is our common language, we must translate and adapt all training materials and selected evaluation indicators into our own languages, so that they can be used with our target populations.…”
Section: Discussionmentioning
confidence: 99%